The Importance of Green Supply Chain Management on Supply Chain Performance and Sustainable Supply Chain Management in the Hotel Industry - Meathawiroon, Chanchai (Journal of Applied Economics and Management Strategy, 2023)
The objectives of this research were: (1) to study the level of green supply chain management in the hotel business. (2) to develop the causal model of green supply chain management, supply chain performance, and sustainable supply chain management. and (3) to study the mediation role of sustainable supply chain management on green supply chain management and supply chain performance. The sample of this study was representatives from 220 hotels. Purposive sampling was used. The questionnaire was used as a research tool. Structural equation modeling statistics were used to test hypotheses. The results show that in this study's sample group, the hotel industry, green supply chain management is moderate. The structural equation model was consistent with the empirical data. The causal relationship can be described that green supply chain management has a direct effect on supply chain performance and sustainable supply chain management. Moreover, green supply chain management influences supply chain performance indirectly. Through sustainable supply chain management, it can be stated that sustainable supply chain management plays a significant role as a mediator. As a result, hotel owners should create policies for service design, collaborate with customers and suppliers, manage the environment within the company, and manage capital with greater environmental awareness because these approaches can help to ensure sustainable supply chain management as well as improved supply chain performance.